Associations between Overweight and Obesity and Asthma Outcomes in Urban Adolescents - Rhee, Hyekyun (J Asthma, 2019)
OBJECTIVE: To examine the prevalence of overweight and obesity in urban adolescents with asthma and to investigate the relationships between anthropometric measures and asthma outcomes including quality of life, asthma control and lung function. METHODS: Adolescents with an asthma diagnosis, 12–20 years-old, were recruited from three urban communities in the United States. Spirometry and anthropometric data including height, weight, and waist circumferences were collected along with questionnaire data measuring quality of life, asthma control, and medication adherence. Body Mass Index (BMI) and waist-height ratio (WHtR) were computed. RESULTS: The sample (N=294) included 48% female and 80% African American. About 50% of the sample were either overweight or obese, and 41% had central obesity. No significant gender interactions with either BMI or WHtR on asthma outcomes were found. Neither BMI nor WHtR predicted quality of life, asthma control or medication adherence, while females had poorer quality of life and asthma control regardless of weight status (p<.001). Higher BMI or WHtR predicted higher spirometry values. Regardless of weight status, females had greater percent predicted spirometry values, while raw values (L) were significantly greater in males. CONCLUSIONS: High BMI is a common comorbidity among poor, primarily African American, urban adolescents with asthma. The negative impact of being overweight or obese on quality of life or asthma control is yet to be manifested in adolescents. The findings underscore adolescence as an ideal period to safely intervene to reduce excessive body weight, which can prevent the potentially harmful effects of obesity on future asthma outcomes.